Systematic Physical-Layer Raptor Coding to Attain Low Decoding Complexity - Li, Guan-Ting; Wu, Hsuan-Kuan; Lee, Huang-Chang; Wang, Hui-Ming; Lin, Mao-Chao (IEEE communications letters, 2018)
We study physical-layer raptor (PLR) coding for message blocks of moderate lengths to achieve low decoding complexity with only a slight degradation in throughput. Approaches include systematic PLR code construction, convergence analysis, and an early termination strategy that is only appropriate for the systematic PLR code.